El Comunicado de prensa: la Anticipada Sentencia en Sede Constitucional - Bedoya Ramírez, Daniela (2023)
Being aware of the respect for the rights from the procedural point of view imposed to the Constitutional Court by our Constitution, the purpose of this research paper has its focus on a very special procedural form we decided to call Advanced Verdict: The Press Release. This is und erstood as the act of communication that in Colombia the Constitutional Court repeatedly applies to communicate the meaning and scope of their decisions, without having signed the text of the verdict, and therefore not having shattered the procedural stage of notification. The main objective of the research is to demonstrate how in reality this practice creates uncertainty and confusion in the community, over the broadcasting of the Constitutional Court’s decisions through press releases, with which evades the implementation of basic procedural rules of public order which guideline actions throughout the process justified under Article 64 of the Law 270 of 1996, that on the contrary are not of compulsory application. The work is divided into three structu ral axes as follows: first, Symbolic or Norm Efficacy of the press releases; second, Procedure of the Public Action of Unconstitutionality; and third, the Principle of Legal Certainty. Analyzed by representative cases: Case of the Justice and Peace Law, Cr iminal Procedure Code Case, Case of property regime between same - sex couples, decriminalization of abortion Case and the referendum promoter of the second presidential reelection Case.